DIPLOMASI BUDAYA INDONESIA MELALUI ASIAN GAMES 2018 - Dinda Ayu Sabrina; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research will explain the cultural diplomacy carried out by Indonesia through The XVIII Asian Games which was held in 2018. Asian Games 2018 took place in Indonesia, and for the first time in history, Asian Games 2018 was held in two cities, Jakarta and Palembang. As a country with rich culture, Indonesia takes advantage of Asian Games 2018 as a moment to carry out cultural diplomacy in order to build nation branding to the international community.This research uses constructivist perspective, cultural diplomacy theory, and nation branding concept. The method used in this research is a qualitative descriptive method. Meanwhile, data collection is done by using library research technique which consists of books, journals, news, and websites with reliable credibility. This research proves that Indonesia has carried out cultural diplomacy through Asian Games 2018 to build its nation branding. Cultural diplomacy carried out by Indonesia can be seen from various aspects; (1) Asian Games 2018 pre-event; (2) The official theme song for Asian Games 2018; (3) Logo and mascot for Asian Games 2018; (4) The Asian Games 2018 opening ceremony; (5) Culinary during Asian Games 2018; (6) The Asian Games 2018 medal; (7) People, institution, and apparatus of Indonesia itself.Keywords: Asian Games 2018, Spirit of Indonesia, Cultural Diplomacy, Nation Branding